A new prediction model for lateral cervical lymph node metastasis in patients with papillary thyroid carcinoma: Based on dual-energy CT. Issue 145 (December 2021) - Zou, Ying; Sun, Shuangyan; Liu, Qian; Liu, Jihua; Shi, Yan; Sun, Fang; Gong, Yan; Lu, Xiudi; Zhang, Xuening; Xia, Shuang
Graphical abstract: Highlights: DECT parameter could predict lateral lymph node metastasis in papillary thyroid carcinoma. The new nomogram could facilitate the prediction risk with an AUC up to 0.912. Individualized lateral lymph node dissection could be performed based on the nomogram. Abstract: Purpose: The current study aimed to develop and validate a prediction model to estimate the independent risk factors for lateral cervical lymph node metastasis (LLNM) in papillary thyroid carcinoma (PTC) patients based on dual-energy computed tomography (DECT). Method: This study retrospectively conducted 406 consecutive patients from July 2015 to June 2019 to form the derivation cohorts and performed internal validation. 101 consecutive patients from July 2019 to June 2020 were included to create the external validation cohort. Univariable and multivariable logistic regression analyses were used to evaluate independent risk factors for LLNM. A prediction model based on DECT parameters was built and presented on a nomogram. The internal and external validations were performed. Results: Iodine concentration (IC) in the arterial phase (OR 2.761, 95% CI 1.028–7.415, P 0.044), IC in venous phase (OR 3.820, 95% CI 1.430–10.209, P 0.008), located in the superior pole (OR 4.181, 95% CI 2.645–6.609, P 0.000), and extrathyroidal extension (OR 4.392, 95% CI 2.142–9.004, P 0.000) were independently associated with LLNM in the derivation cohort. These four predictors were incorporated into the nomogram. The model showed good discrimination in the derivation (AUC, 0.899), internal (AUC, 0.905), and external validation (AUC, 0.912) cohorts. The decision curve revealed that more advantages would be added using the nomogram to estimate LLNM, which implied that the lateral lymph node dissection was recommended. Conclusions: DECT parameters could provide independent indicators of LLNM in PTC patients, and the nomogram based on them may be helpful in treatment decision-making.